Kinerja Penyuluh Pertanian dalam Meningkatkan Kapasitas Petani di Kabupaten Bone Kecamatan Barebbo Desa Carowalie - Salman Salman; Helda Ibrahim; Musdalipa Musdalipa (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Agricultural extension workers play a strategic role in supporting agricultural development by enhancing farmers’ capacity as the main actors in the agricultural sector. The success of this process is strongly influenced by the performance of extension workers in delivering extension services that are responsive, accountable, and oriented toward service quality. This study aims to analyze the performance of agricultural extension workers in improving farmers’ capacity in Bone Regency, Barebbo District, Corawalie Village. The research employed a descriptive design using a qualitative approach supported by simple quantitative analysis. Data were collected through observation, interviews, documentation, and questionnaires involving 45 farmer respondents, and were analyzed using thematic analysis and a Likert scale percentage index. The results indicate that the overall performance of agricultural extension workers is categorized as high, with an average score of 80.76%. Service quality achieved the highest score, followed by responsiveness and responsibility. These findings demonstrate that extension workers have effectively provided services, assistance, and problem-solving support, which contribute to improving farmers’ capacity in managing their farming activities. The study implies that strengthening the performance of agricultural extension workers is essential to enhance farmers’ independence and professionalism in achieving sustainable agricultural development.